The Nanking Massacre: Analysis of Japanese and Chinese Interpretation and Remembrance of Nanking 1940s-The Present - Gordon, Josh (My University, 2014)
This study examines the 1937 Nanking massacre and the atrocities, it focuses on how the events that took place in Nanking have affected the way history in Japan and China is written. This essay will shed light upon the effects of the Nanking Massacre in Japanese and Chinese historiography of the event by examining the various historiographies of each country in regards to the massacre. This study takes an analysis of why there are failing parallels between how China and western societies review the incident versus Japan's interpretation. To help facilitate the dispute between what happened and how the massacre is remembered in regards to Nanking, this study will examine a court debate in the 1970's of a one hundred man killing contest amongst Japanese officers, Japan's education system of the early eighties and nineties where history textbooks used in Japanese high schools were found to have language that isolated, that is, the language used in Japanese texts books used language that perceived Japan as a non-aggressor in the Second Sino-Japanese War, as well as some of the knowledge of what happened in Nanking in 1937 not being fully analyzed studied to the extent of which the rest of the world remembered the incident. I will synthesize my own interpretation and provide my opinion on what reasons produced the failing parallels amongst Japanese and Chines historians and politicians alike. Primary sources include Wilson Family Papers, Documents on the Rape of Nanking and The Dissenting Opinion of Radhabinod Pal. Some secondary sources include articles related to the Nanking Massacre and Japanese Education Ministry such as Isolating knowledge of the Unpleasant: The Rape of Nanking in Japanese High School textbooks, The Nanjing Massacre: in History and Historiography.
Keywords: Nanking Massacre, Nanjing, Jiangsu Sheng, China, 1937--Historiography; Historiography--China; Historiography--Japan; Nanjing (Jiangsu Sheng, China)--History--20th century--Historiography